DIMENSI AKSES EKONOMI SYARIAH PADA BISNIS START UP - Herlina (Program Studi Ekonomi Syariah, 2021)
The sharia economic master plan in Indonesia for the period 2019 - 2024 focuses on efforts to increase the size of the halal industry production. The dimension of sharia economic access is more about measuring the ability to use the sharia economy in various sectors, in this journal it is concentrated on startup businesses. This study aims to examine some literature and data on the phenomenon of the emergence of startup businesses. This research belongs to the category of library research with a qualitative approach and uses a descriptive level of explanation. The form and type of research are categorized as phenomenology. When the research was conducted in April 2021. Key informants and informants are the relation of researchers engaged in start-up business. Data collection was carried out by means of interview and observation. Exposure data and reviewed from the research location are classified as reference studies, data analysis which is supported by scholarship using literature / literature in the form of books, journals and relevant sources. The results of the research obtained are that there is a need for the development of knowledge in expanding the start-up business by carrying out marketing activities using social and digital media in order to reach target markets and anticipate competition. An important point in marketing is to distribute information and disseminate products in the start-up business to all segments or circles of society. The use of the market must be controlled by entrepreneurs in the start-up business sector, especially playing positive opportunities that exist around or in the environment. The conclusion of this study is that the pattern of access to Islamic economics in start-up businesses must use clear procedures and performance by describing in detail about product weaknesses or deficiencies, optimal service, clear, polite and still in the corridor of Islamic ethics. The form of sharia economic access to start-up businesses still adheres to Islamic rules and regulations. The dimension of sharia economic access is very much needed by adhering to the halalness of products and making transactions.